Justice meets justification: Women's need for holistic ministry in world mission. Issue 1 (January 2017) - Warner, Shawna; Dzubinski, Leanne M; Wood, Sarah; Martin, Colleen
Missiology continues to be a male-dominated field, despite the fact that the majority of mission practitioners are women. Christian female scholar-practitioners have unique insights into issues facing women in contexts around the world that can be best met through holistic ministry; however, the voices of women scholar-practitioners are often overlooked due to muted group theory and unconscious gender bias. The honor–shame worldview that permeates many societies creates conditions that are especially challenging for women. This article presents the findings of field research and interviews conducted by female scholar-practitioners in MENA, Thailand, and Indonesia, highlighting women's concerns in those specific contexts. We discuss three issues common across these regions, including gendered expectations, educational opportunities, and geographical challenges. Implications for mission practitioners as well as for future research are discussed.